Consumer preferences and willingness to pay for dried traditional mangos from Kitui – A marketing analysis for Kenya and Germany - Uckert, Götz; Cavicchi, Andrea; Soika, Jil; Matavel, Custodio; Mule, Mirriam; Lerantilei, Salama; Turoop, Losenge; Mutia, Temi; Ronner, Esther; Mithöfer, Dagmar; Sieber, Stefan (Frontiers in Sustainable Food Systems, 2023)
The Kenyan mango value chain faces high post-harvest losses due to poor market access alongside a lack of storage technologies and processing facilities. Thus, using fruit processing methods, like solar drying, can enhance shelf life and help smallholder farmers access new markets, diversifying income and livelihoods. Nonetheless, the processing of both indigenous and grafted mango fruits is not a very common practice. This study was conducted to support product development targeting processing and marketing to link farmers to both local and export markets. Four independent consumer testing and sensory evaluation rounds on Kitui’s dried mango flakes were conducted in Germany and Kenya. Data were collected via a group tasting by 31 randomly selected participants and an online questionnaire of 304 randomly selected participants. All participants were given samples of different varieties of dried mango flakes with and without additives. Results show that high-quality mango cultivars, like Ngowe, receive high hedonic scores without any additives (honey, sodium metabisulfite, or ascorbic acid). Some varieties positively respond to the treatments and achieve higher scores, e.g. Van Dyke or the indigenous variety Kikamba. The consumers testing in Germany show that extrinsic attributes, such as organic production, fair trade, cooperative, and sustainable labelled flakes open up new opportunities for farmers who aim for the export market. Against findings derived from German panellists, in Kenya, consumers do not show a higher willingness to pay despite having a positive attitude toward sustainability. Thus, the local market should focus on cost-reduction strategies rather than introducing standardization.